THE ESSENCE AND STRUCTURE OF THE READINESS OF THE FUTURE TEACHER OF PHYSICAL CULTURE FOR THE PROFESSIONAL ACTIVITY OF FORMING THE MORAL QUALITIES OF YOUNGER SCHOOL STUDENTS (Physical Culture and Sport: Scientific Perspective, 2024)
The article proposes ways to involve future teachers of physical culture in various types of educational activities in order to develop their readiness for professional self-improvement; the results of the research can be used for the development of educational and methodological support in order to improve the professional training of future teachers of physical culture.The need for our research is determined by: the need for a highly qualified teacher who is constantly self-improving; the state of the practice of pedagogical education, which is mainly focused on the professional training of future specialists and which does not sufficiently emphasize the formation of their need for self-improvement; the importance of using the entire potential of educational activities in higher education in order to activate the self-improvement of the personality of the future teacher.The relevance and expediency of the scientific study of the mentioned problem is strengthened by the need to eliminate the identified contradictions that objectively take place in the modern theory and practice of the formation of readiness for self-improvement of future physical culture teachers: awareness of the need to create conditions for professional self-improvement of future physical culture teachers in a higher educational institution and insufficient the development of pedagogical support for this process; the need to modernize the structure of educational activities of the higher education institution in accordance with the requirements for specialists in the field of education that have changed and the prevalence of traditional methods of teaching and training future teachers; today's requirements for a specialist in the field of physical education, on the one hand, and insufficient readiness for professional self-improvement of future teachers of physical education, on the other.
Keywords: readiness; future physical culture teacher; moral qualities